2016
DOI: 10.1016/s0140-6736(16)00276-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evidence for the effect of pay-for-performance in primary care on mortality in the UK: a population study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 35 publications
2
97
0
5
Order By: Relevance
“…Furthermore, reanalysis of the data suggested not only that the initial reduction was not statistically significant but also that mortality rates for nonincentivized conditions increased (62). Similarly, mortality rates for conditions not incentivized under the QOF increased in the United Kingdom relative to other countries during the early years of the scheme, although this increase was not statistically significant (86).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, reanalysis of the data suggested not only that the initial reduction was not statistically significant but also that mortality rates for nonincentivized conditions increased (62). Similarly, mortality rates for conditions not incentivized under the QOF increased in the United Kingdom relative to other countries during the early years of the scheme, although this increase was not statistically significant (86).…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies examining the impact of QOF on mortality found no clear association between practice performance and mortality rates (61) or any apparent benefit to the United Kingdom in terms of reduced mortality for incentivized conditions (86). This evidence comes despite a nationwide, multibillion pound scheme that focused specifically on secondary prevention for several major chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The present research suggests that QOF's commodification process is an important unintended consequence, which further questions its continuity (Checkland et al, 2008;Ryan et al, 2016). For instance, the NHS Scotland has substituted QOF entirely by "quality circles" schemes.…”
Section: Discussionmentioning
confidence: 78%
“…These programs aim at improving quality and promoting increased access to health services. The Portuguese experiences of 2008 [4][5][6][7][8] and British experience of 2004 and 2010 [9][10][11][12][13][14] have suggested positive conclusions and indicated some precautions in the application of this strategy, and improvement of the initial results of the contractualized goals was noted. These authors alert to the need to change the agreed indicators every two or three years, to avoid ethical biases with what is called "gaming", that is, the focus of the health teams in achieving contractualized goals and paying less attention to other non-contractual aspects.…”
Section: In Item (Iv)mentioning
confidence: 99%